Pulmonary interstitial glycogenosis within a discrete pulmonary lesion mimicking congenital pulmonary airway malformation - Robert L. Ricca; Adam B. Goldin; Gail H. Deutsch; Kimberly J. Riehle (Elsevier, 2015)
Interstitial lung diseases (ILD) are a heterogeneous group of pulmonary disorders that are relatively rare in the pediatric population. These diseases are characterized by impaired gas exchange and typically manifest with diffuse infiltrates on radiographs. Pulmonary interstitial glycogenosis (PIG) has recently been identified as an ILD affecting neonates and infants that manifests diffusely throughout the lungs by imaging, has non-specific clinical features, and usually has a favorable outcome in the absence of significant comorbid conditions. We report two cases of PIG that presented with focal radiographic abnormalities, leading to erroneous diagnoses of congenital pulmonary airway malformations and pulmonary resection.